CORRELATION OF Ki67 EXPRESSION TO DEGREE OF DYSPLASIA IN LINGUAL EPITHELIAL DYSPLASIA IN Rattus norvegicus EXPOSURED BY CIGARETTE SMOKE (Hubungan Ekspresi Ki67 Terhadap Derajat Displasia Pada Epitel Mukosa Lidah Rattus norvegicus yang Dipapar Asap Rokok) - Rina Kartika Sari; Hening Tuti Hendarti; Bagus Soebadi; Priyo Hadi; Desiana Radithia; Adiastuti Endah P (ODONTO : Dental Journal, 2019)
Background: Dysplasia is malignant transformation of stratified squamous epithelium characterized by cellular atypia and loss of stratification and maturation. It can caused by cigarette smoke. Measuring the activity of cell proliferation as the beginning of dysplasia is very useful to know the development of malignancy. One of proliferation marker is Ki67 that expressed in all cell cycle phase except G0.Methods: 30 male wistar rats divided into: control grup (n=10), exposed to cigarette smoke for 4 weeks (n=10), 8 weeks (n=10) as much as 20 cigarettes/group/day/exposure used smoking pump. Specimen were stained HE to see dysplasia and Ki67 expression seen immunohistochemically. Statistical analyzed by Spearman correlation.Result: There was an increase in mean of Ki67 expression and significant differences between groups (p=0,000) and also significant difference of degree of dysplasia between groups (p=0,000). There was a strong correlation between Ki67 score to degree of dysplasia (p=0.001).Conclusion: Increased of Ki67 expression proportional to the Increase in degrees of dysplasia